Soluble amyloid precursor proteins in the cerebrospinal fluid as novel potential biomarkers of Alzheimer's disease: a multicenter study - Lewczuk, Piotr; Kamrowski-Kruck, H.; Peters, O.; Heuser, I.; Jessen, F.; Popp, J.; Bürger, K.; Hampel, H.; Frölich, Lutz; Wolf, S.; Prinz, B.; Jahn, H.; et al. (Molecular psychiatry, 2010)
In this report, we present the results of a multicenter study to test analytic and diagnostic performance of soluble forms of amyloid precursor proteins α and β (sAPPα and sAPPβ) in the cerebrospinal fluid (CSF) of patients with different forms of dementing conditions. CSF samples were collected from 188 patients with early dementia (mini-mental state examination⩾20 in majority of cases) and mild cognitive impairment (MCI) in 12 gerontopsychiatric centers, and the clinical diagnoses were supported by neurochemical dementia diagnostic (NDD) tools: CSF amyloidβ peptides, Tau and phospho-Tau. sAPPα and sAPPβ were measured with multiplexing method based on electrochemiluminescence. sAPPα and sAPPβ CSF concentrations correlated with each other with very high correlation ratio (R=0.96, P<0.001). We observed highly significantly increased sAPPα and sAPPβ CSF concentrations in patients with NDD characteristic for Alzheimer's disease (AD) compared to those with NDD negative results. sAPPα and sAPPβ highly significantly separated patients with AD, whose diagnosis was supported by NDD findings (sAPPα: cutoff, 117.4 ng ml−1, sensitivity, 68%, specificity, 85%, P<0.001; sAPPβ: cutoff, 181.8 ng ml−1, sensitivity, 75%, specificity, 85%, P<0.001), from the patients clinically assessed as having other dementias and supported by NDD untypical for AD. We conclude sAPPα and sAPPβ might be regarded as novel promising biomarkers supporting the clinical diagnosis of AD.